2017
DOI: 10.11648/j.ajop.20170506.11
|View full text |Cite
|
Sign up to set email alerts
|

Using Different Techniques in Data Transferring by Optisystem Program

Abstract: Abstract:Nowadays, signal communication is considered as a vital element of our modern daily life. This is due to the need for transmitting large amount of different data types such as text, voice, images, videos, etc. The increase in the volume of data communications requires large data transmission capacity. The data can be transmitted using copper wire, but with low data transmission capacity. To resolve this issue of transmitting large data with a higher signal to noise ratio and larger communication dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The experiment demonstrated that, the effect of the security levels were also influenced the allocation of resources in the network. Jabber, M.A., et al, (2017) [16] used different techniques for the information transmission by optical frameworks. In this specialized world, the sign correspondence was being a fascinating point for analysts and a fundamental need to satisfy the necessities of new progressions.…”
Section: Prior Workmentioning
confidence: 99%
“…The experiment demonstrated that, the effect of the security levels were also influenced the allocation of resources in the network. Jabber, M.A., et al, (2017) [16] used different techniques for the information transmission by optical frameworks. In this specialized world, the sign correspondence was being a fascinating point for analysts and a fundamental need to satisfy the necessities of new progressions.…”
Section: Prior Workmentioning
confidence: 99%